The Facts on file student's thesaurus - McCutcheon, Marc; Hellweg, Paul. (New York : Facts on File, 2000)
Provides synonyms and antonyms for more than 7000 words listed in alphabetical order
First edition edited by Paul Hellweg
Keywords: English language -- Synonyms and antonyms